Asignación del presupuesto público y su relación con la eficacia de la ejecución del gasto público en la Municipalidad Distrital de Punchana, periodo 2019 – 2023 - Correa del Castillo, Percy (2025)
Municipalities as public entities require budget allocations so that they can carry out the activities they program; however, these resources received today must fulfill their public purpose, that is, public spending must be carried out efficiently and effectively to guarantee that their use achieves the expected objectives. The study presented includes the development of a research titled "Public budget allocation and its relationship with the effectiveness of the execution of public spending in the District Municipality of Punchana, period 2019 - 2023", focusing mainly on determining the relationship between the allocation of the public budget and the effectiveness of the execution of public spending; Its implementation involved the use of various techniques as well as an instrument called a data collection sheet that allows its evaluation and respective analysis; It is a quantitative approach, with a non-experimental design of a correlational descriptive level. Finally, it was possible to obtain a strong positive relationship between the variables due to the calculated value of Spearman's Rho correlation coefficient of 0.907.